2017
DOI: 10.3389/fimmu.2017.01613
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Inflammation and Immune Activation Stress the Brain

Abstract: Stress refers to a dynamic process in which the homeostasis of an organism is challenged, the outcome depending on the type, severity, and duration of stressors involved, the stress responses triggered, and the stress resilience of the organism. Importantly, the relationship between stress and the immune system is bidirectional, as not only stressors have an impact on immune function, but alterations in immune function themselves can elicit stress responses. Such bidirectional interactions have been prominentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 347 publications
(441 reference statements)
1
53
0
3
Order By: Relevance
“…Several endogenous hormones are likely to contribute to the communication between the intestinal microbiota and the brain [43]. While the colonic expression of preproglucagon and PYY mRNA remained unaltered by HFD, the expression of both hormones was enhanced by antibiotic-induced microbiota depletion.…”
Section: Antibiotic-induced Microbiota Depletion Had Distinct Effectsmentioning
confidence: 99%
“…Several endogenous hormones are likely to contribute to the communication between the intestinal microbiota and the brain [43]. While the colonic expression of preproglucagon and PYY mRNA remained unaltered by HFD, the expression of both hormones was enhanced by antibiotic-induced microbiota depletion.…”
Section: Antibiotic-induced Microbiota Depletion Had Distinct Effectsmentioning
confidence: 99%
“…Dysbiosis plays a main role in increasing intestinal permeability, which permits passage of bacteria‐derived products such as LPS into the portal circulation. In addition to IBD, dysbiosis, intestinal permeability and the ensuing inflammation, has been associated with numerous diseases including NEC, allergies, nonalcoholic fatty liver disease (NAFLD), cardiovascular disease, rheumatoid arthritis, and numerous neurological disorders such as bipolar, schizophrenia, autism, and Parkinson's . Systemic inflammation was assessed using an inflammatory cytokine protein array that detects 40 different inflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to IBD, dysbiosis, intestinal permeability and the ensuing inflammation, has been associated with numerous diseases including NEC, [67] allergies, [68] nonalcoholic fatty liver disease (NAFLD), [69] cardiovascular disease, [70] rheumatoid arthritis, [71] and numerous neurological disorders such as bipolar, schizophrenia, autism, and Parkinson's. [72] Systemic inflammation was assessed using an inflammatory cytokine protein array that detects 40 different inflammatory cytokines. This approach was chosen to maximize the information we could obtain from the minimal amount of plasma obtained from 10-day-old mice.…”
Section: Dysbiosis Is Associated With Systemic Inflammation and Necromentioning
confidence: 99%
“…Several studies reported that a significant part of metabolites in mammalian blood are derived from the community of intestinal microbiota [55]. Via released molecules such as microbe-associated molecular patterns (MAMPs) and other microbial metabolites, microbiota communicate with other organs [56]. LPS, which belongs to the MAMP family, modulates distant organs via Toll-like receptor 4 (TLR4) action via different mechanisms [56].…”
Section: The Microbial Gut-brain Axismentioning
confidence: 99%
“…Via released molecules such as microbe-associated molecular patterns (MAMPs) and other microbial metabolites, microbiota communicate with other organs [56]. LPS, which belongs to the MAMP family, modulates distant organs via Toll-like receptor 4 (TLR4) action via different mechanisms [56]. Noteworthily, TLR4 is expressed at several levels of the gut-brain axis such as in intestinal epithelial cells, enteric neurons, primary afferent neurons, and several cell populations in the brain (microglia, neurons, astrocytes) [57-60].…”
Section: The Microbial Gut-brain Axismentioning
confidence: 99%